Psychosocial impact on intention to leave among generational cohorts in automotive organizations of Tehran, Iran - Sahraee, Rezvan (2019)
Generational differences in intention to leave have presented new challenges for organizations. The results of national and global surveys have indicated that voluntary turnover is higher among employees from Generation Y compared to other generations, although little is known about how and why the generational differences have contributed to such changes in the patterns of turnover intention. This study aims to determine the psycho-social impacts on intention to leave among generational cohorts, in Tehran, Iran. It examines the effect of value on intention to leave through the mediating effect of motivation, attitude (ATT), subjective norm(SN), and perceived behavioral control(PBC). Moreover, it seeks to identify the moderating effect of generational cohorts on the relationship between all involved factors and intention to leave. A quantitative approach was employed with a descriptive cross-sectional design. Through a multistage cluster method, 588 study subjects were sampled and surveyed from an automotive company. With respect to a response rate of 89%, 523 questionnaires were returned among which 498 were statistically analyzed using AMOS Software. The results showed that there are relationships among value, motivation, TPB constructs (ATT, SN, and PBC) and intention to leave. Motivation mediates the relationship between value and TPB constructs as well as intention to leave. Also, TPB constructs (ATT, SN, and PBC) mediate the relationship between value and motivation, and intention to leave. Moreover, generational cohorts moderate the relationship between value, motivation, TPB constructs (ATT, SN, and PBC) and intention to leave. The findings of this study contribute to the body of literature by identifying the mechanism behind the changes observed over the years in intention to leave among generational cohorts. From organizational point of view, the results would help the directors of organizations control the rate of voluntary turnover of their qualified workers. Theoretically, results suggest that Self-determination Theory and the Theory of Planned Behavior can successfully complement each other to provide more explanation for behavioral intention. Therefore, it is recommended that satisfaction of basic psychological needs for autonomy, competence, and relatedness is a key factor to consider any attempt to predict and prevent turnover intention.